Study Of Changes In The Environmental Function Of The Gegerkalong Girang Road Corridor, Bandung City - Muhammad Syahrizal; Heru Wibowo (Universitas Kebangsaan Republik Indonesia [UKRI], 2020)
The city of Bandung has a special attraction for migrants from other regions to carry out various activities. This is because the city of Bandung was made as a center for education, tourism and culture, a trade center, and also as a center of government in West Java Province. The need for economic improvement in an urban area that was originally not developed and is now developing indirectly there are changes in land use or land use in various ways including by changing the function of the original home to a shop house and even turning into a shop or land commercial. This is influenced by the existence of activities or activities of an educational and religious tourism area where this occurs due to the large number of requests to support activities in the area.